Developmentand Population of an Elaborate Formal Ontology for Clinical Practice Knowledge Representation - Mendes, David (2014)
The Ontology for General Medical Science (OGMS) complemented with the Computer-Based Patient Record Ontology (CPR)is based on several upper ontologies which may have formal ontological relations according to the OBO Foundry principles. These ontologies accordant to the underlying Ontological Realism render a structure with reasoning capabilities that reach further than those possible with logical formalisms alone. We propose to extend carefully the OGMS taking into account the diverse ontological relations found in the recently proposed Basic Formal Ontology V2, FMA and SNOMED-CT as foundational ontologies in order to extract axioms for ontology enrichment from natural language text. With these cautions in mind, using careful instantiation we improve largely the reasoning capabilities over the resulting OWL knowledge base. Most of the clinical practice knowledge is currently recorded in SOAP text format. We extend the OGMS with the CPR structure into an Ontology for General Clinical Practice (OGCP) for the generation of adequate ontologically rich axioms from the SOAP text segments.)